Endurance Capacity and Cardiorespiratory Responses in Sedentary Females During Different Phases of Menstrual Cycle - Bandyopadhyay, A; Dalui, R (Kathmandu University Medical Journal, 2014)
Background Alteration in physical work capacity of females during different phases of menstrual cycle has been reported in different populations. Pertinent data is unavailable in Eastern Indian population. Objectives The present study was aimed to determine the endurance capacity and cardiorespiratory responses during different phases of menstrual cycle in young sedentary females of Eastern region of India. Methods Forty five unmarried young healthy sedentary females (21–25 years) were recruited in the present investigation. Duration of their menstrual cycle was 28–30 days. Cardiorespiratory parameters including the endurance capacity was determined by treadmill running with constant monitoring of heart rate by Polar heart rate monitor. Results The pre-exercise heart rate was significantly higher (P<0.02) in the luteal phase. The peak heart rate was significantly lower (P<0.02) in the flow phase than the follicular and luteal phases. VO2max, O2 pulse, maximum pulmonary ventilation and endurance capacity were significantly lower in the follicular phase. However, the endurance capacity was significantly lower in the flow phase. Pre-exercise systolic and diastolic blood pressure did not exhibit any significant variation in different phases of menstrual cycle. Conclusion Therefore, from the present observations it may be concluded that pre-exercise heart rate and respiratory rate are significantly higher in the luteal phase whereas VO2max, O2 pulse, maximum pulmonary ventilation, endurance capacity and peak heart rate were significantly lower in the follicular phase. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10990 Kathmandu Univ Med J 2012;10(4):25-29